1997
DOI: 10.1038/bjc.1997.50
|View full text |Cite
|
Sign up to set email alerts
|

CODE chemotherapy with and without granulocyte colony-stimulating factor in small-cell lung cancer

Abstract: Summary Sixty-three patients with extensive-stage small-cell lung cancer were randomized to receive either cyclophosphamide, vincristine, doxorubicin and etoposide (CODE) alone or CODE plus recombinant human granulocyte colony-stimulating factor (rhG-CSF). rhG-CSF administration in support of CODE chemotherapy resulted in increased mean total received dose intensity for all drugs (P = 0.03) with a significant improvement in survival (P= 0.004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 16 publications
(6 reference statements)
1
12
0
2
Order By: Relevance
“…Dose-dense chemotherapy with the CODE combination (CDDP -VCR -ADM -ETP) and addition of granulocyte colonystimulating factor (G-CSF) can be safely administered to patients with advanced lung cancer (Murray et al, 1991;Fukuoka et al, 1997). Theoretically, this approach might be suitable for chemosensitive tumours such as small-cell lung cancer and thymoma Coldman, 1983, 1984;Levin and Hryniuk, 1987;Murray, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dose-dense chemotherapy with the CODE combination (CDDP -VCR -ADM -ETP) and addition of granulocyte colonystimulating factor (G-CSF) can be safely administered to patients with advanced lung cancer (Murray et al, 1991;Fukuoka et al, 1997). Theoretically, this approach might be suitable for chemosensitive tumours such as small-cell lung cancer and thymoma Coldman, 1983, 1984;Levin and Hryniuk, 1987;Murray, 1987).…”
mentioning
confidence: 99%
“…Theoretically, this approach might be suitable for chemosensitive tumours such as small-cell lung cancer and thymoma Coldman, 1983, 1984;Levin and Hryniuk, 1987;Murray, 1987). Because some pilot data in Japan suggested that administration of 12 weeks of the CODE chemotherapy was barely feasible, subsequent Japanese trials used a modified schedule, which was shortened to 9 weeks (Fukuoka et al, 1997;Furuse et al, 1998).…”
mentioning
confidence: 99%
“…Fukuoka et al [13] conducted a trial with weekly chemotherapy. Sixty-three patients with ED were randomized to cyclophosphamide, vincristine, doxorubicin, and etoposide (CODE) alone or with G-CSF.…”
Section: Densification Of Chemotherapymentioning
confidence: 99%
“…[2][3][4][5] Although its mechanism for disposition has been studied extensively in rodents, 6) the establishment of a pharmacokinetic/pharmacodynamic model is needed to predict the pharmacological eŠect of rhG CSF in humans. We developed such a model in our previous study and showed that the model enables prediction of increase in the number of neutrophils after administration of rhG CSF to healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%